Kontribusi Pesantren dalam Sosialisasi Fiqih di Kabupaten Jember: The Contribution of Islamic Boarding Schools in Socializing Fiqh in Jember Regency - Saifudin Saifudin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
iqh is a significant part of ubudiyah application in Islam, as it regulates and develops all behaviors. Islamic boarding schools, as centers of Islamic education, also develop and socialize fiqh. Moreover, some Islamic boarding schools consider fiqh as the only true law. The research results on how Islamic boarding schools socialize fiqh to the public are conducted internally, through the socialization process in the school's teaching curriculum. The materials are derived from classical books using various contemporary methods, such as weton, sorogan, even bahsul masail, and through fiqh theater. Fiqh merupakan bagian penting dari penerapan ubudiyah dalam Islam, karena di dalam fiqh semua perilaku diatur dan dikembangkan. Pesantren sebagai pusat pengajaran pendidikan Islam turut mengembangkan dan mensosialisasikan fiqh. Bahkan, terdapat pesantren yang menganggap fiqh sebagai satu-satunya hukum yang benar. Hasil penelitian mengenai cara pesantren mensosialisasikan fiqh kepada masyarakat dilakukan dari dalam pesantren, yaitu melalui proses sosialisasi dalam kurikulum pengajaran pesantren. Materi diambil dari kitab-kitab klasik dengan berbagai metode kontemporer, seperti weton, sorogan, bahkan bahsul masail, serta melalui teater fiqh.